Prevalence and factors associated with job burnout among nurses in China: A cross‐sectional study - Lei Li; Jing Fan; Lili Qiu; Chunyan Li; Xuanye Han; Ming Liu; Shihong Zhao; Ying Wang (Wiley, 2024)
Abstract Aim Many people see nursing as a high‐pressure, high‐risk profession. Therefore, job burnout among nursing staff has become an important topic of study and has received widespread attention worldwide. This research intended to evaluate the frequency of and variables related with work burnout among nurses in public hospitals in China. Design Using a multistage random sample procedure, a cross‐sectional survey was carried out in the eastern, central and western areas of China. Methods The Maslach Inventory‐Human Service Survey and demographic information made up the two sections of the questionnaire. Of the 5250 questionnaires sent, 4865 were deemed legitimate, yielding an effective response rate of 92.67%. A linear regression analysis was performed to investigate the variables linked to nursing work burnout. Results Among the 4865 nurses, women accounted for 97.4% of the survey respondents, most of whom were aged 26-35 years. Results showed that the total scores of emotional exhaustion (EE), depersonalization (DP) and reduced personal accomplishment (PA) were 20.02 ± 12.04, 4.78 ± 5.54 and 34.42 ± 10.32 respectively. 50.7% of subjects obtained high or moderated scores on EE, 32.8% of subjects obtained high or moderated scores on DP and 80.4% of subjects obtained low or moderated scores on PA. Age, department, position, post‐establishment, work shift type in recent months, overtime times in recent months and night shift frequency in recent months were negatively correlated with EE, and child status, monthly income, working days per week and sleep quality in recent 1 month were positively correlated with it (F = 141.827, P < 0.01, R2 = 0.243). Age, gender, department, post‐establishment, overtime hours in recent months and night shift frequency in recent months were negatively correlated with DP, and child status and sleep quality in the last 1 month were positively correlated with it (F = 78.794, p < 0.01, R2 = 0.115). Child status, years of nursing work and sleep quality in the last 1 month were negatively correlated with PA, whereas age, position, work shift type in recent months and night shift frequency in recent months were positively correlated with it (F = 67.981, p < 0.01, R2 = 0.089).